Investigating credit transmission mechanism in the Republic of Macedonia: Evidence from Vector Error Correction Model - Milan Eliskovski (National Bank of the Republic of Macedonia, 2018)
Research subject of this paper is the credit transmission mechanism in the Republic of Macedonia or in other words this paper investigates the effects of the monetary signals by the National Bank of the Republic of Macedonia on banks' lending. The credit transmission is analyzed through its narrow nature or so called bank lending channel. In order to explain how the bank lending channel operates in Macedonia, two theoretical models are considered and econometrically tested. The first one is the traditional bank lending channel explained by Bernanke and Blinder model and the second one is the credit rationing model by Stiglitz and Weiss. The econometric technique employed is the vector error correction model or known as Johansen cointegration technique which is appropriate for empirical testing based on time series. The empirical results suggest that the Stiglitz and Weiss model better explains the banks' behavior in the Republic of Macedonia, that is the banking sector is risk averse and rations loans with an aim not to deteriorate its' profitability. Therefore, monetary tightening signals clearly affect the banks to restrict lending. On the other hand, the monetary expansionary signals have to be supported by favorable balance sheet structure of the banks as well as by favorable macroeconomic conditions in order to encourage lending.
Keywords: C22; E52; E58; G21; 330; bank lending channel; monetary transmission; credit rationing; VECM analysis